Implementation of the Bullying Box and Establishment of Prevention Team to Address Bullying Cases at SMA Islam Al-Azhar 30 Salatiga - Cahya Wulandari; Sukadari, Sukadari; Winarsih, Winarsih; Rahmayani, Chanidia Ari; Hassan, Muhamad Sayuti; Aditya, Agung (Indonesian Journal of Legal Community Engagement, 2025)
Bullying in Indonesia is increasingly on the rise, especially among children and teenagers, and most of it occurs in school environments. Bullying that occurs to a student will affect their psychological and social development and raise concerns about their health in the future. The problem faced by the students of SMA Islam Al-Azhar 30 Salatiga is the prevalence of bullying experienced by students, perpetrated by their own peers, both individually and in groups. This is due to the students' lack of knowledge, which stems from insufficient attention and education about bullying provided by parents and the school. The service team help solve the Partner's problem by creating a bullying box as a place for students to report bullying behavior they have experienced, witnessed, or heard, and by forming a bullying prevention and resolution team or violence prevention team. The purpose of this activity is to help prevent and resolve bullying among students at SMA Islam Al-Azhar 30 Salatiga.